Trends in severe traumatic brain injury in Victoria, 2006–2014. Issue 11 (20th June 2016) - Beck, Ben; Bray, Janet E; Cameron, Peter A; Cooper, D James; Gabbe, Belinda J
Abstract: Objective: To describe the incidence and causes of hospitalisation for severe traumatic brain injury (TBI) in Victoria over a 9‐year period. Design, setting and participants: A retrospective review of data from the population‐based Victorian State Trauma Registry for hospitalised cases of severe TBI, 2006–2014. Main outcome measures: Temporal trends in the incidence of severe TBI and in causes of injury. Results: There were 2062 patients hospitalised with severe TBI in Victoria during the 9‐year study period. The incidence of severe TBI declined significantly over this period, from 5.0 to 3.2 cases per 100000 population per year, mainly because of reductions in severe TBI resulting from motor vehicle crashes (incidence rate ratio [IRR], 0.89; 95% CI, 0.86–0.92; P < 0.001), which largely involved people in the 15–34‐year‐old age group (64.7%). A decline was also observed in severe TBI in motorcyclists, but this was not statistically significant (IRR, 0.94; 95% CI, 0.89–1.00; P = 0.06). The incidence of severe TBI resulting from low falls, which occurred mostly in people aged 65 years or more (68.1%), increased (IRR, 1.04; 95% CI, 1.00–1.08; P = 0.03). The overall incidence of severe TBI resulting from intentional events was 0.60 cases per 100000 population, and declined over the study period (IRR, 0.95; 95% CI, 0.91–1.00; P = 0.03). Conclusions: The decline in the incidence of motor vehicle‐related severe TBI suggests that road injury prevention measures have been effective. Additional targeted measures for reducing the incidence of major head injuries from falls should be explored.